The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.12740/psychiatriapolska.pl/online-first/2
|View full text |Cite
|
Sign up to set email alerts
|

Indirect self-destructiveness in homosexual individuals

Abstract: The research results indicate that, as compared with the group of heterosexual individuals, in the group of homosexuals there occurs a worsening in psychological functioning, which may be also manifested by an increased indirect self-destructiveness index. The increased intensity of indirect self-destructiveness in homosexual individuals may be considered a manifestation of worsened psychological functioning. The homosexual individuals look after their health similarly to heterosexuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…Results of other studies carried out in Poland and Brazil confirm behaviours related to risky sexual practices, attitudes and conducts among young people with minority sexual orientations (MSOs) (i.e. lesbian, gay, bisexual and transgender youth) in comparison to heterosexual young people (Brignol et al 2015, Tsirigostis et al 2015.…”
Section: Introductionmentioning
confidence: 73%
“…Results of other studies carried out in Poland and Brazil confirm behaviours related to risky sexual practices, attitudes and conducts among young people with minority sexual orientations (MSOs) (i.e. lesbian, gay, bisexual and transgender youth) in comparison to heterosexual young people (Brignol et al 2015, Tsirigostis et al 2015.…”
Section: Introductionmentioning
confidence: 73%
“…Furthermore, positive correlation was observed between the masculinity scale and indirect self-destructiveness in women, whereas negative correlation was found between indirect self-destructiveness and the femininity scale in men [1]. …”
Section: Resultsmentioning
confidence: 99%
“…1, 12]. Most of the carried out research concerned direct self-destructiveness; it was found, for instance, that women exhibit passive self-destructiveness [13].…”
Section: Introductionmentioning
confidence: 99%
“…Overeating may in some cases be considered a self-destructive mechanism leading ultimately to death due to complications of obesity. In one study involving self-destructive behaviour, it was shown that the predominant psychological gender was undetermined type [21].…”
Section: Discussionmentioning
confidence: 99%